(untitled) (London Journal of Research In Science: Natural and Formal, 2023)
Climate change is a concept that is directly correlated with everyday life. Extreme weather events are occurring with greater intensity and frequency, most likely caused by an increase in the Earth’s average temperature. Dozens of studies have been based on the anthropogenic contribution of the increase in greenhouse gases, which are identified as the main cause of global warming. But what is the contribution of the human species itself as a biological factor in this increase?